In vivo vascularization and islet function in a microwell device for pancreatic islet transplantation. (21st April 2021) - Smink, Alexandra M; Skrzypek, Katarzyna; Liefers-Visser, Jolanda A L; Kuwabara, Rei; de Haan, Bart J; de Vos, Paul; Stamatialis, Dimitrios
Abstract: Islet encapsulation in membrane-based devices could allow for transplantation of donor islet tissue in the absence of immunosuppression. To achieve long-term survival of islets, the device should allow rapid exchange of essential nutrients and be vascularized to guarantee continued support of islet function. Recently, we have proposed a membrane-based macroencapsulation device consisting of a microwell membrane for islet separation covered by a micropatterned membrane lid. The device can prevent islet aggregation and support functional islet survival in vitro . Here, based on previous modeling studies, we develop an improved device with smaller microwell dimensions, decreased spacing between the microwells and reduced membrane thickness and investigate its performance in vitro and in vivo . This improved device allows for encapsulating higher islet numbers without islet aggregation and by applying an in vivo imaging system we demonstrate very good perfusion of the device when implanted intraperitoneally in mice. Besides, when it is implanted subcutaneously in mice, islet viability is maintained and a vascular network in close proximity to the device is developed. All these important findings demonstrate the potential of this device for islet transplantation.